Concordance among hematopathologists in classifying blasts plus promonocytes: A bone marrow pathology group study. (16th April 2020) - Foucar, Kathryn; Hsi, Eric D.; Wang, Sa A.; Rogers, Heesun J.; Hasserjian, Robert P.; Bagg, Adam; George, Tracy I.; Bassett, Roland L.; Peterson, LoAnn C.; Morice, William G.; Arber, Daniel A.; Orazi, Attilio; et al.
Abstract: Enumeration of blasts and promonocytes is essential for World Health Organization (WHO) classification of myelomonocytic neoplasms. The accuracy of distinguishing blasts, promonocytes and monocytes, including normal vs abnormal monocytes, remains controversial. The objective of this analysis is to assess concordances between experienced hematopathologists in classifying cells as blasts, promonocytes, and monocytes according to WHO criteria. Each of 11 hematopathologists assessed glass slides from 20 patients [12 with chronic myelomonocytic leukemia (CMML) and 8 with acute myeloid leukemia (AML)] including blood and BM aspirate smears, and limited nonspecific esterase (NSE) stains. All cases were blindly reviewed. Fleiss' extension of Cohen's kappa for multiple raters was used on these variables, separately for peripheral blood (PB) and bone marrow (BM). Spearman's rank correlation was used to assess correlations between each pair of hematopathologists for each measurement. For the classification based on the sum of blasts and promonocytes in the BM, Fleiss' kappa was estimated as 0.744. For PB, categorizing patients according to the sum of blasts and promonocytes, Fleiss' kappa was estimated as 0.949. Distinction of abnormal monocytes from normal monocytes in PB did not achieve a good concordance and showed strong evidence of differences between hematopathologists ( P < .0001). The hematopathologists achieved a good concordance rate of 74% in CMML vs AML classification and a high k rate, confirming that criteria for defining the blasts equivalents (blasts plus promonocytes) could be applied consistently. Identification of monocyte subtypes (abnormal vs normal) was not concordant. Our results support the practice of combining blasts/promonocytes into a single category.